METHOD FOR ASSESSING THE LEVEL OF CYBERSECURITY ENHANCEMENT OF CRITICAL INFRASTRUCTURE OBJECTS OF THE STATE - Korchenko, Oleksandr; Ivanchenko, Evgenia; Bakalinsky, Oleksandr; Myalkovskyi, Danylo; Zubkov, Denys (Science-based technologies, 2024)
Due to the increasing cybersecurity threats, especially to a state's critical infrastructure, there is a growing need for the development and implementation of effective methods for assessing the level of cybersecurity. The critical infrastructure of a state (such as energy, transportation, medical facilities, etc.) is becoming increasingly dependent on information technologies. Security breaches in these technologies can have serious consequences for citizens' lives and health, as well as economic losses. Many countries are imposing various regulatory requirements regarding cybersecurity, such as GDPR in the European Union or NIST in the United States. This compels organizations managing critical infrastructure to actively seek and implement effective methods for assessing cybersecurity levels. The rapid technological progress leads to the emergence of new attack methods, necessitating the allocation of various resources (financial, human, time, etc.) to develop new, more effective means of enhancing cybersecurity. Assessing the level of cybersecurity enhancement will subsequently allow for evaluating the effectiveness of resources invested in security. The developed method for assessing the enhancement of cybersecurity levels of critical infrastructure objects of the state is based on a model of a characteristic system aimed at assessing the state of cybersecurity in Ukraine. It involves procedures for forming linguistic variables, interval fuzzification, building benchmarks, forming sets of inspection object characteristics, the primary measurement process, forming basic pairs and associative rules, and visualization of results. These are formalized into respective stages, enabling the implementation of the process of assessing the cybersecurity state of critical infrastructure inspection objects. The described method can become an effective tool for analyzing and evaluating the level of cybersecurity of the state's critical infrastructure with the aim of ensuring national security and protection against cyber threats. Further development should focus on building a system that allows for automating the process of assessing the enhancement of cybersecurity levels at inspection objects.